Potential Combination of Cinnamon Type C. Burmanii with C. Cassia as an Antibacterial Alternative in Perineal Wound Infection (Laboratory Study of S. Haemolyticus Culture of Perineum Wounds) - Citra Adityarini Safitri (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Use and misuse of antibiotics in puerperal infections can trigger the emergence of resistant bacteria. To overcome antibiotic resistance, tannin compounds, flavonoids and alkaloids in cinnamon serve as a safe antibacterial with fewer side effects. Objective Proving the combination of C. Burmanii with C. cassia as an antibacterial alternative to perineal wound infection. Methods Laboratory experiments in vitro. The study group was divided into 2 groups, namely the treatment group concentrations of 1.25%, 2.5%, 5% and 10%, the control group used Amoxicillin 500 mg. Data analysis using ANOVA test was then with Tukey HSD test. Results ANOVA test results were obtained 0.00 in the bacterium S. haemolyticus. p-value = 0.000 (<0.05) where antibacterial in cinnamon shows a significant difference in the zone of the killing of S.haemolyticus bacteria in perineal wound infection. Conclusions and Recommendations Tannin compounds, flavonoids and alkaloids in a combination of cinnamon are effective as an antibacterial alternative to perineum wound infections. clinical trial research is needed with experimental animal research subjects with a toxicity test to ensure that the extract is safe to use in experimental animals.